Congenital Neonatal Intestinal Obstruction: Retrospective Analysis at Tertiary Care Hospital - Vijay Singh; Manish Pathak (EL-Med-Pub, 2020)
Background: The purpose of this study is to analyze the etiology, clinical presentation and outcome of neonatal intestinal obstruction at our institute. Materials and Methods: The medical record of all the patients, presented with intestinal obstruction in neonatal period during 2014 and 2015 was reviewed retrospectively for etiology, clinical features, investigations, management, and outcome. Results: Out of total 53 cases of neonatal intestinal obstruction, 27 were of intestinal atresia (9 cases (17%) were of duodenal atresia, 7 (13%) were of jejunal atresia and 8 (13%) were ileal atresias and 3 cases were found with colonic atresia); 7 were malrotation, 17 were Hirschsprung's disease (HD). All the patients were investigated with abdominal radiography and sonography. All patients were managed surgically. Overall mortality was 10/53 (18.8%). Out of 27 cases of atresia, 9 patients died (33% mortality). Septicemia was the cause of death in 7 patients (58.3%). Anastomotic leak was present in one mortality case. Conclusion: The most common cause of neonatal intestinal obstruction is atresia. Duodenal atresia was the most common atresia in our study followed by ileal atresia. Postoperative complications like septicemia led to most of deaths in our series. Septicemia, wound infection, hypothermia, prematurity need special attention for survival of neonates.